Creativity and innovation in Iceland: Individual, environmental, and cultural variables. Issue 1 (2nd January 2017) - Kerr, Barbara A.; Birdnow, Maxwell; Hallaert, Jenelle; Alexander, Keely; Malmsten, Robyn; Stull, Olivia; Wright, J. D.; Lucas, Brittany; Swanson, Rachel; Claiborn, Grace J.
ABSTRACT: This comprehensive literature review (CLR) is an analysis and synthesis of literature, observations, interviews, and artifacts as a means to answer the question, "Why is Iceland so innovative?" Iceland is considered by international indices as a leading nation in innovation in many fields, including design, music, art, and literature. A team of doctoral-level students and master's-level counselors studying the psychology of creativity collected information regarding individual ability and personality in Iceland as well as the natural, physical, and social environment variables that might be related to creativity and innovation. The creativity literature supported the idea that ability and personality attributes of Icelanders might be the source of Icelandic innovation. The popular literature often referred to an environment of extremes and natural beauty that inspires higher rates of creativity and innovation. The scholarly literature pertaining specifically to Iceland suggested instead that open and egalitarian families; innovation education curricula and free play; cultural support for creativity; and government policies were the main drivers of innovation in Iceland. The researchers' observations found that interviewees often disputed the literature, particularly regarding the impact of high ability, natural environment, and policy on innovation, and that artifacts supported most environmental variables.